The fish - MacLeod, Heather, 1958- ([Chicago] : Childrens Press, 1995)
After waiting and waiting, a child catches a fish -- only to take pity on it and throw it back.
1.5
K-3
Keywords: Fishing -- Fiction; Fishing -- Fiction